Answer:
(4, 7/2)
Step-by-step explanation:
Take the mean of the x-coordinates and the mean of the y-coordinates.
x = (-1 + 9)/2 = 8/2 = 4
y = (2 + 5)/2 = 7/2
Answer: (4, 7/2)
Answer:
y = 4
x = -6
Step-by-step explanation:
multiply first equation by 3
3×(5x+4y)= -14 ➡ 15x + 12y = -42
multiply second equation by -5
-5×(3x+6y)= 6➡ -15x -30y = -30
now add both equations up
15x +12y -15x -30y = -42 -30 (15x will eliminate -15x)
-18y = -72
y = 4 use this to find value of x
3x + 6×4 = 6 ➡ ex = -18 ➡ x = -6
355 ~ 350
102~ 100
350
- 100
= 250
Answer:
the answer is H because it is h
Answer:
false
Step-by-step explanation: